Peningkatan Pengetahuan dan Keterampilan Latihan Keseimbangan pada Lansia untuk Pencegahan Risiko Jatuh - Dyah Ayu Fatmawati; Dinda Nafilla; Muhammad Husein Syawaludin; Fauziah Rezkiyati; Melly Anisa Putri; Jeri Novaro Sumual; Wendelinus Imus; Khairina Zulfah; Nafi’ah; Chania Eka Sintani; Eko Ardian; Anissa (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
Aging is associated with decreased muscle strength, motor coordination, and body balance, which increases the risk of falls among older adults. This community service program aimed to improve older adults' knowledge and balance exercise skills as a strategy for fall prevention. The program involved 30 older adults and consisted of health education and balance exercise training. Educational materials covered fall risk factors, the importance of physical activity, and static and dynamic balance exercises guided by a physiotherapist. Program effectiveness was evaluated using pre-test, post-test, and direct observation of participants' exercise performance. The results showed that the average knowledge score increased from 61.3 to 84.7, with 25 participants (83.3%) demonstrating improved knowledge. In addition, 26 participants (86.7%) were able to perform the balance exercises correctly after the training. Participants also showed high enthusiasm and motivation to continue practicing independently at home. These findings indicate that the program effectively enhanced participants' knowledge and balance exercise skills and has the potential to support fall prevention while improving independence and quality of life among older adults.